Fabrication of high thermal conductive shape-stabilized polyethylene glycol/silica phase change composite by two-step sol gel method. (July 2018) - Weng, Zengsheng; Wu, Kun; Luo, Fubin; Xiao, Fei; Zhang, Qian; Wang, Shan; Lu, Mangeng
Abstract: Tetraethyl silicate (TEOS) and polyethylene glycol (PEG) were used to prepare inorganic–organic polyethylene glycol (PEG)/silica (SiO2 ) nanocomposites by a controllable sol–gel method. Two kinds of counter ions were used to help gelatinize step by step. The presence of metal ions accelerates hydrolysis of SiO2 sol and the presence of ammonium ions allows the system to gel rapidly. PEG forms a shell-and-core structure with SiO2 and this composite shows excellent thermal stability. Moreover, system contains respectively Calcium ions (Ca 2+ ), magnesium ions (Mg 2+ ), aluminum ions (Al 3+ ) were studied. It is very interesting that PEG with different metal ions formed different strength of the chemical force between PEG and metal ions change due to presence of different metal ions. As the force increased, the thermal conductivity increased from 0.25 W m −1 k −1 to 0.41 W m −1 k −1 and the phase change latent heat of the composites increased from 46.99 to 91.05 J/g, without affecting the phase transition temperature.